2020
DOI: 10.1002/er.5679
|View full text |Cite
|
Sign up to set email alerts
|

Phase change material impregnated wood for passive thermal management of timber buildings

Abstract: The Scots pine (Pinus sylvestris L.) sapwood was impregnated with the eutectic mixture of capric acid (CA) and stearic acid (SA) as phase change material (PCM) via vacuum process for passive thermoregulation in timber buildings. The hygroscopic properties, mechanical properties, thermal energy storage (TES) characteristics and lab-scale thermo-regulative performance of wood/ CA-SA composite were evaluated. The produced composite from PCM was morphologically and physico-chemically characterized by SEM, FT-IR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…An optimum mass percentage gain of 29.9 mass% and a latent heat value of 20.62 J g −1 was reported. Temiz et al [24] studied Scots pine sapwood impregnated with an eutectic mixture of capric acid (CA) and stearic acid (SA). After thermal characterization of the material, it was concluded that the system wood/CA-SA can be used for indoor temperature regulation and energy saving in timber buildings.…”
Section: Introductionmentioning
confidence: 99%
“…An optimum mass percentage gain of 29.9 mass% and a latent heat value of 20.62 J g −1 was reported. Temiz et al [24] studied Scots pine sapwood impregnated with an eutectic mixture of capric acid (CA) and stearic acid (SA). After thermal characterization of the material, it was concluded that the system wood/CA-SA can be used for indoor temperature regulation and energy saving in timber buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Solid wood of alder 26 with 29.9 wt% retention of paraffin and coated with polystyrene to prevent leakage of the PCMs showed a latent heat value of 20.62 J/g. Temiz et al 27 studied Scots pine sapwood impregnated with a eutectic mixture of capric acid (CA) and stearic acid (SA). After thermal characterization of the material, it was concluded that the system wood/CA‐SA can be used for indoor temperature regulation and energy saving in timber constructions.…”
Section: Introductionmentioning
confidence: 99%
“…In Anatolia, wood is expressed as a most versatile raw material that is needed from cradle to grave. Wood has been used for thousands of years and has emerged as an important sustainable building material to potentially replace steel and concrete because of its economic and environmental advantages, which include energy savings, low carbon emissions (15 kg/m 3 ), and high carbon storage (250 kg/m 3 ) (Wimmers 2017;Temiz et al 2020). The popularity of the use of wood in space is also increasing.…”
Section: Introductionmentioning
confidence: 99%